Analisis Karakteristik Passenger Traffic Di Bandara Radin Inten Ii Lampung Tahun 2022 - Delina, Ellyce Laura (Jurnal Sistem Transportasi & Logistik, 2023)
Transportation is an important part of people's lives. Lampung Province is one of the provinces that has a strategic position to increase the capacity and capability of air transportation modes. The aim is to identify the characteristics of passengers at Radin Inten II Airport. the demographic characteristics produced are 21-30 years old, with male gender, and have an income of IDR 5,000,000 - IDR 10,000,000 where on average are private employees and students/students. From the results of the correlation analysis, it is known that what fulfills the demand for passengers to choose flights are work, income, transportation used to the airport, travel destination, and flight hours.